RSK2 promotes melanoma cell proliferation and vemurafenib resistance via upregulating cyclin D1 - Wu, Hai-Zhou; Li, Lan-Ya; Jiang, Shi-Long; Li, Yi-Zhi; Shi, Xiao-Mei; Sun, Xin-Yuan; Li, Zhuo; Cheng, Yan (Frontiers in Pharmacology, 2022)
BRAF inhibitors are commonly used in targeted therapies for melanoma patients harboring BRAFV600E mutant. Despite the benefit of vemurafenib therapy, acquired resistance during or after treatment remains a major obstacle in BRAFV600E mutant melanoma. Here we found that RSK2 is overexpressed in melanoma cells and the high expression of RSK2 indicates poor overall survival (OS) in melanoma patients. Deletion of RSK2 inhibits cell proliferation and sensitizes melanoma cells to vemurafenib. In addition, the overexpression of RSK2 results in vemurafenib resistance. Mechanistically, RSK2 enhances the phosphorylation of FOXO1 by interacting with FOXO1 and promoting its subsequent degradation, leading to upregulation of cyclin D1 in melanoma cells. These results not only reveal the presence of a RSK2-FOXO1-cyclin D1 signaling pathway in melanoma, but also provide a potential therapeutic strategy to enhance the efficacy of vemurafenib against cancer.